2004
DOI: 10.1038/sj.onc.1207872
|View full text |Cite|
|
Sign up to set email alerts
|

INK4a/Arf is required for suppression of EGFR/ΔEGFR(2-7)-dependent ERK activation in mouse astrocytes and glioma

Abstract: Amplification of the epidermal growth factor receptor (EGFR) or expression of its constitutively activated mutant, DEGFR(2-7), in association with the inactivation of the INK4a/Arf gene locus is a frequent alteration in human glioblastoma. The notion of a cooperative effect between these two alterations has been demonstrated in respective mouse brain tumor models including our own. Here, we investigated underlying molecular mechanisms in early passage cortical astrocytes deficient for p16 INK4a / p19 Arf or p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As far as we are aware, there are no existing studies into human glioblastomas in the literature which associate this fact to the activation of ERK1/2. In cell lines derived from mouse glioma models, the resistance to down‐regulate the MAPK pathway in the absence of INK4a/ARF was confirmed 40 . For these authors, the deletion of INK4a/ARF appears to keep ERK in its active, phosphorylated state and insensitive to an upstream inhibitor specifically targeting EGFR/ΔEGFR.…”
Section: Discussionmentioning
confidence: 93%
“…As far as we are aware, there are no existing studies into human glioblastomas in the literature which associate this fact to the activation of ERK1/2. In cell lines derived from mouse glioma models, the resistance to down‐regulate the MAPK pathway in the absence of INK4a/ARF was confirmed 40 . For these authors, the deletion of INK4a/ARF appears to keep ERK in its active, phosphorylated state and insensitive to an upstream inhibitor specifically targeting EGFR/ΔEGFR.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings demonstrated that ARF regulates MET in both mouse prostate tumors and PCa cells null for PTEN and p53 genes, a frequent event at the advanced stages of human prostate malignancy (34). Differential to its tumor suppressive role in glioma and melanoma (35), ARF regulates functions and transcriptional activation of oncogenic signaling events in nucleus of cancer cells through multiple mechanisms (36). Thus the details in ARF transition from tumor suppressor to promoter deserve further investigation which may link aging to cancer transformation (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although the dispensability of INK4A has been described for some nevus cells (Michaloglou et al, 2005), INK4A is discussed as main senescence mediator in human nevi (Bennett, 2003;Gray-Schopfer et al, 2006). Even though the link between oncogenic RAS or B-RAF and downstream senescence inducers in melanocytes is unclear, a connection between mitogen activated protein kinase (MAPK) activation and INK4A or ARF has been reported for other cell lines (Aguirre et al, 2003;Lachat et al, 2004;Michaloglou et al, 2005).…”
Section: Introductionmentioning
confidence: 99%